ANALISIS PENGARUH SISTEM PENGENDALIAN INTERN, SISTEM INFORMASI AKUNTANSI PERSEDIAAN BARANG DAN SISTEM INFORMASI AKUNTANSI PENJUALAN TERHADAP PENINGKATAN PENJUALAN ( Studi Kasus Pada PT. Jateng Argo Berdikari ) - Fuad, Syifaul; Mohklas, Mohklas (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2024)
This research aims to find out whether the internal control system, inventory accounting information system and sales accounting information system have an effect on increasing sales. The population in this study were employees of PT. Central Java Argo Berdikari. Sampling was carried out using the census method and the sample size was 73 respondents. The type of data used is primary data. This research uses a questionnaire in collecting data. The test techniques used are validity tests, reliability tests, classical assumption tests including normality tests, multicollinearity tests and heteroscedasticity tests. Hypothesis testing in this study used multiple linear tests with SPSS version 26. The results of this research show that the Internal Control System has no effect and is not significant on increasing sales, the Goods Inventory Accounting Information System has a positive and significant effect on increasing sales and the Sales Accounting Information System has no effect and is not significant on increasing sales. Keywords: Internal Control System, Inventory Accounting Information System, Sales Accounting Information System and Sales Increase.